HYDROPONIC DEVICE FOR HOME - YOON, WOO GUL (2015)
The present invention relates to a hydroponic device for home use, and more specifically, to a hydroponic device which can do various hydroponics within a home, does not receive a restriction for an installation space as the device is not big, and can be ornamentally used as an aquarium or a fish bowl. The hydroponic device comprises: a hydroponic housing (10) having a box shape with a space inside while the entire side is closed and a partial side or the entire side is transparent, having an opening and closing door (11) in one part, and where at least a pair of rails (15) are separately installed for a certain distance while crossing the internal space in parallel; a culture container (20) having a box shape of which an upper end is opened while being arranged in the lower portion of the rails and capable of containing water, having an edge which is surrounded by an external wall (21), and having a drainage hole (23) on the floor of one side as a water containing space is divided into two parts by a partition (22) with the height lower than the height of the external wall; an underwater motor (30) arranged on the floor of the housing, and connected to a water supply pipe (31) for transferring water contained in the lower portion of the housing to the culture container; and a tray (40) having a plate shape with a certain length and a side, having mounting grooves (41) on both sides of a longitudinal direction to be mounted on the rails, and having a plurality of supporting grooves (42) formed inside to support a hydroponic plant. 본 발명은 가정용 수경재배 장치에 관한 것으로, 더욱 상세하게는 가정 내에서 각종 수경재배를 할 수 있으면서도 장치가 비대하지 않아 설치 공간에 제약을 받지 않고, 수족관 또는 어항을 겸할 수 있어서 관상용으로 사용할 수 있도록 할 목적으로, 전체 면이 폐쇄되고 일부 면 또는 전체 면이 투명하게 되며 내부에 공간이 형성된 상자 형태로서, 일부분에 개폐 도어(11)가 형성되고 적어도 한 쌍의 레일(15)이 내부 공간에서 평행하게 가로질러 일정 거리 이격 설치된 수경 하우징(10); 상기 레일의 하부에 배치되고 상단이 개방되며 물 수용이 가능한 상자 형태로서, 가장자리가 외벽(21)으로 둘러싸이고 내부의 물 수용 공간이 상기 외벽의 높이보다 낮은 격벽(22)에 의해 두 부분으로 구획되어 일측 바닥면에 배수공(23)이 형성된 재배통(20); 상기 하우징의 바닥에 배치되어 하우징 저부에 수용된 물을 상기 재배통으로 이송하는 급수관(31)과 연결된 수중 모터(30); 일정 길이와 면을 가진 판 형태로서 상기 한 쌍의 레일 상에 안착되도록 길이방향의 양 변에 거치홈(41)이 형성되고 내측에는 수경식물을 지지하도록 복수 개의 지지홀(42)이 형성된 트레이(40);를 포함하여 이루어진 수경재배 장치에 관한 것이다.